Characterization of Hypervirulent Klebsiella pneumoniae (Hv-Kp): Correlation of Virulence with Antimicrobial Susceptibility - V. Vandhana; K. Vishwas Saralaya; Sevitha Bhat; Shalini Shenoy Mulki; Archana. K. Bhat (International Journal of Microbiology)
Introduction. Hypervirulent K. pneumoniae (Hv-Kp) is an emerging variant of classical K. pneumoniae (C-Kp) that exhibits hypermucoviscocity and possesses multiple siderophores as virulence factors and is known to cause serious debilitating infections in immunocompetent individuals. Aim and objective. The aim of this study is to identify C-Kp and Hv-Kp strains and detect their virulence factors and antimicrobial susceptibility patterns. Materials and Methods. A total of 129 K. pneumoniae isolates from different clinical samples were used for the identification and differentiation of classical K. pneumoniae (C-Kp) and hypervirulent K. pneumoniae (Hv-Kp) to correlate their virulence with antimicrobial susceptibility patterns and identify their risk factors. Hypermucoviscosity was determined by a string test (>5 mm of string length). The aerobactin gene was detected by PCR. Results and Conclusion. In total, 13.9% (18/129) were Hv-Kp and 86.1% (111/129) were C-Kp. Only 50% (9/18) of the Hv-Kp isolates were hypermucoviscous. C-Kp was significantly more resistant to antimicrobials than Hv-Kp. Among C-Kp, 75.7% were ESBL producers and 76.6% were multidrug resistant while in Hv-Kp, 44.44% were both ESBL producers and multidrug-resistant which is statistically significant (P<0.01). Diabetes was a common risk factor for C-Kp infections whereas, respiratory disorders like COPD and prolonged ICU stay were the risk factors for Hv-Kp infections. The mortality rate among patients with Hv-Kp infections (87.5%) was significantly high when compared to that of C-Kp infections (35.7%) (P<0.001). A majority of hypermucoviscous K. pneumoniae isolates were multidrug resistant (65.2%). Although the prevalence of Hv-Kp infections was low, a high percentage of them were multidrug resistant with a significantly high mortality rate. Hence, it is important to efficiently identify Hv-Kp strains from clinical samples and determine their antimicrobial susceptibility patterns, so as to provide immediate and effective treatment and to prevent possible outbreaks.